2014
DOI: 10.1111/jsap.12270
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall reconstruction with latissimus dorsi and an autologous thoracolumbar fascia graft in a dog

Abstract: A new technique for autogenous chest wall reconstruction using a latissimus dorsi muscle flap and a free graft of thoracolumbar fascia was utilised in a two-year-old Dobermann after resection of a high-grade osteosarcoma from the left thoracic wall. En bloc excision of the chest wall mass, including six ribs, was performed. The resulting chest wall defect was too large to be reconstructed with only a pedicled muscle flap and was reconstructed with a latissimus dorsi muscle flap cranially and a free graft of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Bongartz et al reported that the most frequent complication associated with use of FL for perineal herniorrhaphy was lameness in the donor limb. In a single case where TLF was used as a source of autologous tissue for chest wall reconstruction in a dog, there was a positive outcome, with no donor site morbidity or postoperative complications . Future research into whether the same postoperative complications are associated with TLF grafts as with FL grafts is necessary to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Bongartz et al reported that the most frequent complication associated with use of FL for perineal herniorrhaphy was lameness in the donor limb. In a single case where TLF was used as a source of autologous tissue for chest wall reconstruction in a dog, there was a positive outcome, with no donor site morbidity or postoperative complications . Future research into whether the same postoperative complications are associated with TLF grafts as with FL grafts is necessary to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…When addressing large body wall defects, several options for primary repair can be considered, including direct apposition of the wound edges when possible, harvest and placement of an autogenous fascial or muscle flap, or use of exogenous materials such as surgical meshes, synthetic patches, and various biological materials …”
Section: Discussionmentioning
confidence: 99%
“…When addressing large body wall defects, several options for primary repair can be considered, including direct apposition of the wound edges when possible, harvest and placement of an autogenous fascial or muscle flap, or use of exogenous materials such as surgical meshes, synthetic patches, and various biological materials. 1,2 Direct apposition of the wound edges is often not possible due to the size of the defect and the tension that results upon closure. Therefore, in many instances, reconstruction with either autogenous or exogenous structural materials is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary practice, the thoracolumbar fascia and fascia lata have been used for the reconstruction of various tissues like oral cavity mucosa, esophagus and urethra [11][12][13][14][15]22] . In the traditional cutaneous trunci myocutaneous composite flap, it has been reported that, when the flap is lifted, the latissimus dorsi and subcutaneous tissue between should not be included in the flap [8] .…”
Section: öZer Karabağli Uğurlumentioning
confidence: 99%
“…For this purpose, the most commonly used fascial tissues in veterinary practice are the thoracolumbar fascia and fascia lata [14,15] .…”
Section: Introductionmentioning
confidence: 99%